Impact of O-H···π Hydrogen Bond on IR and NMR Parameters of Cannabidiol: Theoretical and Experimental Study - Aneta Buczek; Kacper Rzepiela; Teobald Kupka; Małgorzata A. Broda (Molecules)
This study investigates the influence of weak hydrogen bonds on the conformational properties and spectral characteristics of cannabidiol (CBD). Using a combination of FTIR and NMR spectroscopy, we analyze the effects of intramolecular hydrogen bonding, particularly the O-H∙∙∙π interactions, on the molecular behavior of CBD in chloroform solution. FTIR spectra reveal distinct νs(O-H) stretching bands at 3603 cm−1 and 3425 cm−1, corresponding to free and hydrogen-bonded -OH groups, respectively, with experimental results aligning closely with computational data for CBD conformers. Notably, conformer 1a predominates in solution, with weaker hydrogen bonding observed for the -OH(B) group compared to -OH(A). Additionally, the formation of -OH∙∙∙π hydrogen bonds affects key vibrational bands in the 1700–1300 cm−1 region. NMR analysis shows significant shifts in proton and carbon signals, emphasizing the influence of hydrogen bonding on CBD’s electronic environment. The observed changes in coupling constants, although subtle, further highlight the impact of these interactions on spin–spin coupling. Overall, these findings provide deeper insights into the structural and electronic factors governing CBD’s behavior in solution, offering a basis for future studies on hydrogen bonding in biomolecules and their pharmacological implications.